Identifikasi Unsur Radioaktif Pada Batako Ringan Aerasi Citicon Dengan Metode Laser Induced Breakdown Spectroscopy (LIBS) - Wahyulianti, Wahyulianti; Ratini, Ni Nyoman; Balik Sudarsana, I Wayan (BULETIN FISIKA; Vol 17 No 1 (2016): BULETIN FISIKA, 2016)
Research has been done to identify the radioactive elements in the Citicon aerated lightweight concrete block sample. In this research used a Citicon aerated lightweight concrete block as a sample with 1 cm x 3 cm in size and identification process used LIBS method. Radioactive elements identified in Citicon aerated lightweight concrete block the LIBS method were Th, Ra, and K. The number of photon emission intensity at the wavelength of each element is 396.710 nm, 620.033 nm, and 766.497 nm respectively by 62.33 a.u, 1.67 a.u, and 72.75 a.u.